2008
DOI: 10.1097/aud.0b013e318177d9ac
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Perception of Tinnitus

Abstract: Our interpretation of the findings is that personality influences the persistence of tinnitus by influencing the tendency to be aware of it. Consideration of personality factors may improve the ability to tailor tinnitus therapies, and the concept of awareness may benefit treatment outcomes by showing tinnitus sufferers a means of internalizing the locus of control over their symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 35 publications
4
55
0
1
Order By: Relevance
“…Conflicting reports exist regarding their relationship from previous studies. Some authors report that tinnitus comorbidities are unrelated to age 30 and others report significant differences in gender regarding tinnitus annoyance and HRQoL of sufferers 9,31 . Female patients in our study scored higher in mental distress scales compared to the males irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting reports exist regarding their relationship from previous studies. Some authors report that tinnitus comorbidities are unrelated to age 30 and others report significant differences in gender regarding tinnitus annoyance and HRQoL of sufferers 9,31 . Female patients in our study scored higher in mental distress scales compared to the males irrespective of age.…”
Section: Discussionmentioning
confidence: 99%
“…For example most police officers and soldiers are exposed to acoustic trauma but only some of them complain about tinnitus. It was suggested that there are two components of reporting tinnitus by patients: first, the necessary physiological or pathological conditions to provide a stimulus to the auditory cortex, and second the personal tendency to report a tinnitus as present [31]. There is a relation between personality and perception of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Folmer et al [35] found no significant difference in reported tinnitus loudness between tinnitus clinic patients with and without current depression, but an association between depression and reported tinnitus severity was found. Personality factors and different coping ability may explain the findings [36,37]. Differences in attentional mechanisms and cognitive characteristics might also influence how tinnitus is perceived [38][39][40].…”
Section: Discussionmentioning
confidence: 99%